2014
DOI: 10.1016/j.molimm.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Altered DNA methylation profile in Norwegian patients with Autoimmune Addison's Disease

Abstract: Autoimmune Addison's Disease (AAD) is an endocrine and immunological disease of uncertain pathogenesis resulting from the immune system's destruction of the hormone producing cells of the adrenal cortex. The underlying molecular mechanisms are largely unknown, but it is commonly accepted that a combination of genetic susceptibility and environmental impact is critical. In the present study, we identified multiple hypomethylated gene promoter regions in patients with isolated AAD using DNA isolated from CD4+ T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 92 publications
0
9
0
2
Order By: Relevance
“…In a recent study, Bjanesoy et al (29) identified multiple hypomethylated gene promoter regions in CD4 + T cells isolated from PAI patients. Given that in vitro treatment of NK cells with demethylating agents has been shown to result in decreased surface expression of NKG2D (30), it would be of interest for future studies to examine the DNA methylation profile of NK cells from PAI patients, focusing primarily upon the promoters of genes that encode NK cell activatory receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Bjanesoy et al (29) identified multiple hypomethylated gene promoter regions in CD4 + T cells isolated from PAI patients. Given that in vitro treatment of NK cells with demethylating agents has been shown to result in decreased surface expression of NKG2D (30), it would be of interest for future studies to examine the DNA methylation profile of NK cells from PAI patients, focusing primarily upon the promoters of genes that encode NK cell activatory receptors.…”
Section: Discussionmentioning
confidence: 99%
“…This therapy fails to provide the anticipatory rise of cortisol prior to wakening and thus gives a shifted circadian profile while also resulting in acute nonphysiological levels of cortisol in the middle of the day 132 . Patients have altered immune responses in the form of altered circadian patterns of circulating monocytes and natural killer cells 133 , impaired natural killer cell function 134 and hypomethylated CD4+ T cells 135 . In an attempt to rectify these adverse outcomes, modified and dual release preparations 133,136,137 , as well as continuous 138 and pulsatile pump (The Pulses study, ISRCTN67193733) preparations are being trialled.…”
Section: Potential Mechanisms Underlying This Inhibition Include Disrmentioning
confidence: 99%
“…DNA methylation involves the addition of a methyl group to cytosines by DNA methyl transferases (Dnmts) [74]. DNA methylation varies among tissues and cell type because it is a dynamic process involving methylation and demethylation events [75,76].…”
Section: Dna Dna Methylationmentioning
confidence: 99%